2015
DOI: 10.1002/elps.201500333
|View full text |Cite
|
Sign up to set email alerts
|

Protein immobilization on the surface of polydimethylsiloxane and polymethyl methacrylate microfluidic devices

Abstract: PDMS and PMMA are two of the most used polymers in the fabrication of lab-on-chip or microfluidic devices. In order to use these polymers in biological applications, it is sometimes essential to be able to bind biomolecules such as proteins and DNA to the surface of these materials. In this work, we have evaluated a number of processes that have been developed to bind protein to PDMS surfaces which include passive adsorption, passive adsorption with glutaraldehyde cross-linking, (3-aminopropyl) triethoxysilane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…An et al reported a facile method for the construction of cross-linked polyelectrolyte multilayers using PSS/PAH by post-implantation and subsequent photochem [ 34 ]. PAH/PSS layer-by-layer assembly containing nanoporous silver submicrocubes were developed for electrochemical glucose sensing [ 35 ], while PEI/PAA polyelectrolyte multilayer architecture coated on PDMS conducted to long-term stability on the interface for protein detection [ 37 ].…”
Section: Recent Developments In Polyelectrolyte Coatingsmentioning
confidence: 99%
“…An et al reported a facile method for the construction of cross-linked polyelectrolyte multilayers using PSS/PAH by post-implantation and subsequent photochem [ 34 ]. PAH/PSS layer-by-layer assembly containing nanoporous silver submicrocubes were developed for electrochemical glucose sensing [ 35 ], while PEI/PAA polyelectrolyte multilayer architecture coated on PDMS conducted to long-term stability on the interface for protein detection [ 37 ].…”
Section: Recent Developments In Polyelectrolyte Coatingsmentioning
confidence: 99%
“…Amino groups can bind to the activated carboxylic groups of the proteins. Zero‐length carbodiimide cross‐linkers such as 1‐ethyl‐3‐(‐3‐dimethylaminopropyl) carbodiimide hydrochloride (EDC or EDAC) are usually used to activate the carboxylic groups by creating O‐acylisourea intermediate. They react rapidly to the amino groups of the surface producing isourea as a by‐product.…”
Section: Glass‐based Microfluidic Devicesmentioning
confidence: 99%
“…Previous works, including ours, have followed a similar approach but were focused on silicon silanization and detection of different biological targets. 38,39,43 While some studies have been using APTES on PDMS without prior activation of the surface, 32,44 it has been shown that activating the PDMS surface right before silanization would increase the grafting efficiency. 45,46 To the best of our knowledge, no comprehensive study related to controllable and stable direct PDMS silanization by APTES has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Only a minority of devices include a biosensitive surface inside a microfluidic channel as it requires a reproducible and stable surface chemistry for biomolecule conjugations. Silanization reactions have been shown to be a convincing method for PDMS bonding, surface modification for molecular grafting, , or even for preventing biofouling . Silanization of PDMS relies on readily producible silanol groups for covalent bonding of silane molecules.…”
Section: Introductionmentioning
confidence: 99%